HIV Vaccine Trial Exploits a Dual and Central Role for Innate Immunity - Fuller, Deborah Heydenburg (American Society for Microbiology, 2014)
Limited understanding of correlates of protection from HIV transmission hinders development of an efficacious vaccine. D. J. M. Lewis and colleagues (J. Virol. 88:11648–11657, 2014, doi:10.1128/JVI.01621-14) now report that vaginal immunization with an HIVgp140 vaccine linked to the 70-kDa heat shock protein downregulated the human immunodeficiency virus (HIV) coreceptor CCR5 (chemokine [C-C motif] receptor 5) and increased expression of the HIV resistance factor APOBEC3G (apolipoprotein B mRNA-editing, enzyme-catalytic, polypeptide-like 3G), in women. These effects correlated with HIV suppression ex vivo. Thus, vaccine-induced innate responses not only facilitate adaptive immunity–they may prove to be critical for preventing HIV transmission.